Gold Nanoparticles/Carbon Nanotubes and Gold Nanoporous as Novel Electrochemical Platforms for L-Ascorbic Acid Detection: Comparative Performance and Application - Tasca-Gottardo, F; Tasca-Gottardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Herein, the effects of nanostructured modifications of a gold electrode surface in the development of electrochemical sensors for L-ascorbic acid detection have been investigated. In particular, a bare gold electrode has been modified by electrodeposition of gold single-walled carbon nanotubes (Au/SWCNTs) and by the formation of a highly nanoporous gold (h-nPG) film. The procedure has been realized by sweeping the potential between +0.8 V and 0 V vs. Ag/AgCl for 25 scans in a suspension containing 5 mg/mL of SWCNTs in 10 mM HAuCl4 and 2.5 M NH4Cl solution for Au/SWCNTs modified gold electrode. A similar procedure was applied for a h-nPG electrode in a 10 mM HAuCl4 solution containing 2.5 M NH4Cl, followed by applying a fixed potential of −4 V vs. Ag/AgCl for 60 s. Cyclic voltammetry and electrochemical impedance spectroscopy were used to characterize the properties of the modified electrodes. The developed sensors showed strong electrocatalytic activity towards ascorbic acid oxidation with enhanced sensitivities of 1.7 × 10−2 µA µM−1cm−2 and 2.5 × 10−2 µA µM−1cm−2 for Au/SWCNTs and h-nPG modified electrode, respectively, compared to bare gold electrode (1.0 × 10−2 µA µM−1cm−2). The detection limits were estimated to be 3.1 and 1.8 µM, respectively. The h-nPG electrode was successfully used to determine ascorbic acid in human urine with no significant interference and with satisfactory recovery levels. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.